En quoi se constitute Ie pouvoir de la société civile? Une analyse sur la base de l'exemple de l'économie collaborative - Dreher, Julia (2019)
Abstract: With the introduction of the internet into society, the latter has changed fundamentally: all societal spheres seem to undergo crises, to mean that structures need to be changed in order to adapt to newly emerging contexts. From media using online tools to report on news to the world, and societal groups, e.g. organizations of disadvantaged people empowering each other via online connection and communication, to political issues such as climate change, where social movements emerge on a much larger scale than ever before: contemporary society is confronted with a degree of complexity that calls for new ways of how to interact and communicate. The research presented here is based on the assumption that civil society is particularly and better capable of dealing with this new form of informational complexity which a society strongly influenced by the internet has to deal with in general. Furthermore it is based on the assumption of an understanding of power that incurs the idea of ac